IDENTIFIKASI DESIGN ANTROPOLOGI PADA KAWASAN DESA WISATA MELIKAN - Wahyu Setyaningrum; Edward E. Pandelaki; Atik - Suprapti (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: Melikan Village as a tourist village for pottery craftsmen is the only one in the world with an oblique rotation technique. This village is unique in its anthropological design. This study will discuss how the design anthropology in Melikan Village, which can be seen from the regional design pattern, its composition, the designation function so as to form a relationship of form-function-meaning in the region. The method used is descriptive with journals and books that discuss the anthropology of the Melikan Village area, accompanied by direct observation and study of the state of the Melikan tourist village. Some of the theories used are: figure ground theory, linkage, form and symbols, as well as the forming elements of urban planning which are used to analyze the macro and micro (building) as form-function-meaning relation (region). From the research carried out, it can be concluded that there is a correlation between the form-function-meaning of anthropology found in the Melikan Tourism Village Area. In macro: such as the existence of figure ground theory, Linkage, shapes and symbols, as well as elements of urban planning, In micro (residents' houses,showrooms and Sunan Pandanaran’s mosque) there are several similarities in the shape of the building (Adjusting the state of the room), Building structures that use structures and roofs to adjust the shape of the house, Facades are made of woven bamboo and some of the bricks and ornaments, some of which use earthenware columns, as well as in mosque buildings found in the form of buildings that are symmetrical and taller than the surrounding area, the canopy roof structure containing the crown as a symbol of Allah's power, simple facades and windows made of wood, and ornaments on the door with plant motifs symbolizing closeness to nature. There is integration between residents' houses as a center for pottery craftsmen, a showroom and the Sunan Pandanaran mosque. Abstrak: Desa Melikan sebagai desa wisata pengrajin gerabah satu-satunya di dunia dengan teknik Putaran Miring, desa ini memiliki kekhasan dalam hal desain antropologinya. Kajian ini akan membahas bagaimana antropologi design yang ada di Desa Melikan, yang dapat dilihat dari pola desain wilayah, komposisinya, fungsi peruntukan sehingga membentuk hubungan dari bentuk-fungsi-makna di wilayah tersebut. Metode yang digunakan adalah deskriptif dengan jurnal dan buku yang membahas antropologi kawasan Desa Melikan ini, disertai dengan observasi dan studi langsung keadaan Desa Wisata Melikan. Beberapa teori yang digunakan seperti: teori figure ground, linkage, form dan symbol, serta elemen pembentuk tata kota yang digunakan untuk menganalisis relasi bentuk-fungsi-makna ruang secara makro (Wilayah) dan mikro (Bangunan). Dari penelitian yang dilakukan dapat disimpulkan bahwa ada korelasi antara bentuk–fungsi–makna antropologi yang terdapat di Kawasan Desa Wisata Melikan: seperti adanya teori figure ground, keterkaitan (Linkage), bentuk dan simbol, serta elemen pembentuk tata kota, pada bangunan rumah warga dan showroom terdapat beberapa kesamaan pada bentuk bangunan (Menyesuaikan keadaan ruang), Struktur bangunan yang menggunakaan struktur dan atap menyesuaikan bentuk rumah, Fasad terbuat dari anyaman bambu dan beberapa dari bata serta ornamen ditemui pada rumah tinggal ada yang menggunakan kolom dari gerabah, serta pada bangunan masjid ditemui berupa bentuk bangunan yang simetris dan lebih tinggi dari daerah di sekitarnya, struktur atap tajuk yang terdapat mahkota sebagai simbol kekuasaan Allah, fasad yang sederhana dan jendela yang terbuat dari kayu, serta ornamen pada pintu yang bermotif tanaman melambangkan kedekatan dengan alam. Adanya integrasi antara rumah warga sebagai sentra pengrajin gerabah, showroom dan Masjid Sunan Pandanaran.